Improving maize yield in newly reclaimed soils: effects of irrigation, mulching, and foliar treatments - Ahmed M. Abdelghany; A. S. Farouk; E. Sh. Alwakel; Mohamed Ebaid; Mahmoud Naser; Sobhi F. Lamlom; A. A. Shehab (BMC Plant Biology)
Abstract Improving maize yield in newly reclaimed soils presents major challenges. This study analyzed the impact of various irrigation methods (drip, sprinkler, and surface), foliar applications (potassium bicarbonate (PoB), methanol, and water control), and mulching techniques (with and without rice paddy straw) on the growth, physiology, productivity, and water use efficiency (WUE) of maize in newly reclaimed soil over the two seasons of 2022 and 2023. The study employed a split-split plot design arranged in randomized complete blocks with three replications. The integration of drip irrigation, PoB foliar spray, and rice paddy straw mulching yielded superior results, improving grain yield (GY,10.0-13.08 t/ha) and biological yield (BY, 51.37–59.53 t/ha) in comparison to control treatments. The findings were validated through various multivariate analyses, such as principal component analysis (PCA), structural equation modeling (SEM), hierarchical clustering heatmap, and radar plot visualization. The findings of PCA revealed that the initial two components accounted for 85.6% of the total variance, with growth and yield parameters exhibiting a strong correlation with the first principal component (76.8%). Also, SEM analysis revealed that BY (0.603), plant height (0.594), and net assimilation rate (0.589) exerted the most significant direct positive influences on GY. Drip irrigation demonstrated the highest WUE at 3.70 kg/m³, significantly surpassing sprinkler irrigation at 3.32 kg/m³ and surface irrigation at 3.03 kg/m³. Mulched plots showed better WUE (3.53 kg/m³) compared to non-mulched plots (3.17 kg/m³), with PoB application yielding the highest WUE (3.80 kg/m³). Seasonal variations were noted, with drip irrigation combined with mulch and PoB reaching the highest WUE (4.20 kg/m³) in the first season, whereas sprinkler irrigation with mulch and PoB demonstrated better performance (5.49 kg/m³) in the second season. The results highlight the opportunity to enhance maize yields in newly reclaimed soils, with the integration of drip irrigation, potassium bicarbonate foliar application, and rice straw mulching emerging as the most innovative practice for boosting crop performance and optimizing water use.